Endeudamiento y rentabilidad en la empresa procesadora de alimentos y su relación con la estabilidad económica, período 2017 - 2018. - Alvaro Cojitambo, Monica Estefania (My University, 2020)
In this work, a case analysis was carried out whose purpose was to determine the level of indebtedness and profitability of the Pronaca CA National Food Processor, through the financial reasons applied to the controlled financial statements of the Superintendence of Companies for the 2017-2018 period, to establish the relationship with the economic stability of the company. Therefore, it will be used as indicators of indebtedness to the ratio of debt, equity debt, and interest coverage; the profitability that are the ratio of gross profit margin, net, operational and return on assets and equity. Taking into account its specific objectives that are the evaluation of the levels of indebtedness through the ratio of debt, debt - equity and interest coverage, also assess the levels of profitability through the gross profit margin, operating profit, net profit ratio, return on assets (ROA) and return on equity (ROE) in order to analyze the economic stability of the company through the indicators. The company must evaluate its financial situation in order to know in this case: How to influence the indebtedness and profitability in the economic stability of the Food Processing Company? And in this way to be able to make correct decisions or improve in some indebtedness process in order to efficiently take care of its resources. The national food processing company Pronaca CA will be dedicated to elaborate and produce food from the field to the table, for all people either inside or outside the country, for this reason it is of great importance to know the economic level of the same, it was carried out this investigation taking information from the Superintendence of Companies, since this is public information for anyone who needs. With respect to the variables proposed, the work applies quantitative modality research, as it is the technique to collect numerical data to understand the behavior or know the purpose of the investigation; and the qualitative that they are to analyze and explain on the subject besides being able to be represented in figures, images among others. Considering also that the study methodology was the bibliography that refers to research through scientific articles, information from books or others; also the analytical that is a key part because each result of the investigation was analyzed and compared to know about it. However, given the knowledge of all these processes and factors that influence the production of these products, it is totally clear that a company must know and know how to manage its financial resources, through tools that help and ensure the use of these, as they are the indicators of indebtedness and profitability for the correct decision making. As a result, through the financial indicators in relation to the economic stability of the company, it is at a favorable point because its levels of indebtedness and profitability are controlled and optimally managed by its part, what happens as a consequence that it generates more profit and profit to continue operating in the market. The results obtained from the evaluation of the profitability indicators determine that the gross margin from one period to another decreased in a few parts even though it is not favorable for the company, in operating margin it is favorable due to the increase in profits, the net margin such the same is favorable; the return on the asset in the same way as on the liability are favorable for the company which means that there will be more profits for it. Given the results established through the financial indicators in relation to the economic stability of the company, it is at a favorable point because its levels of indebtedness and profitability are controlled and optimally managed by its part, which happens as a consequence that. This generates more profit and profit to continue operating in the market. Therefore, it is concluded that the application of financial indicators are fundamental tools to know, analyze the economic and financial situation of the company, in this case the company is at a favorable point, in this way it is also recommended not exceeding the levels of indebtedness, in addition to maintaining the optimal level of sales to generate profits in order to be economically stable and stay in the market. Given the results in the level of indebtedness it is recommended not to exceed the recommended levels for each indicator, also to maintain the level of coverage of interest in order to cover with the financial expenses that are maintained on a day-to-day basis, also a highly revised planning and analyzed when handling some financing with third parties. With regard to profitability levels, it is recommended not to neglect the level of gross profit since this is given depending on the level of sales that is maintained in the company, likewise its levels of net and operational profit should be reviewed in relation to its benefits economic, in the same way the returns on assets and equity are required to periodically measure the efficiency of their administration. This work is carried out thanks to the media, since the financial information of the food processor is obtained on the website of the Superintendence of Companies, because this is public information and available to anyone who needs it according to the Organic Law on Transparency and Access to Public Information, as a goal the information obtained is of utmost importance for the development of research. After examining, analyzing and knowing these results, the benefit of these processes will be to make the right decisions to maintain the continuity of the company and thus maintain a stable economic profitability, fulfilling purposes and goals, which will help the development of the same and even of the economic situation of the country because there is a demand and supply within the market.
En el presente trabajo se realizó un análisis de casos cuyo propósito fue determinar el nivel de endeudamiento y rentabilidad de la Procesadora Nacional de Alimentos Pronaca C.A, mediante las razones financieras aplicadas a los estados financieros obtenidos de la Superintendencia de Compañías del periodo 2017-2018, para establecer la relación con la estabilidad económica de la empresa. Por lo cual, se utilizaron como indicadores de endeudamiento a la razón de deuda, deuda patrimonio, y la cobertura de intereses; lo de rentabilidad que son la razón de margen de utilidad bruta, neta, operacional y rendimiento sobre activo y patrimonio. Teniendo en cuenta sus objetivos específicos que son evaluar los niveles de endeudamiento mediante la razón de deuda, deuda – patrimonio y cobertura de intereses, también evaluar los niveles de rentabilidad mediante la razón margen de utilidad bruta, utilidad operacional, utilidad neta, rendimiento sobre activos (ROA) y rendimiento sobre patrimonio (ROE) para así poder analizar por medio de los indicadores la estabilidad económica de la empresa. La empresa debe evaluar su situación financiera para así conocer en este caso: ¿Cómo influye el endeudamiento y rentabilidad en la estabilidad económica de la empresa Procesadora de Alimentos? Y de esta manera poder tomar decisiones correctas o mejorar en algún proceso de endeudamiento para así cuidar de manera eficiente los recursos de la misma. La empresa Procesadora Nacional de Alimentos Pronaca C.A se dedica a elaborar y producir alimentos del campo a la mesa, para todas las personas ya sea dentro o fuera del país, por esta razón es de gran importancia conocer el nivel económico de la misma, se realizó esta investigación tomando información de la Superintendencia de Compañías, ya que esta es información pública para cualquier persona que las necesite. Con respecto a las variables planteadas, el trabajo aplica la investigación de modalidad cuantitativa, por ser la técnica para recolectar datos numéricos para comprender el comportamiento o conocer el fin de la investigación; y la cualitativa que son para analizar y explicar sobre el tema además de poder representarse en figuras, imágenes entre otras. Considerando también que la metodología de estudio fueron la biografía que se refiere a la investigación por medio de artículos científicos, información de libros u otros; también la analítica que es parte clave debido a que cada resultado de la investigación fue analizado y comparado para conocer sobre el mismo. No obstante dado el conocimiento de todos estos procesos y factores que influyen dentro de la producción de estos productos, queda totalmente en claro que una empresa debe conocer y saber manejar sus recursos financieros, mediante herramientas que ayudan y aseguran la utilización de estos, como lo son los indicadores de endeudamiento y rentabilidad para la correcta toma de decisiones. Como resultado por medio de los indicadores financieros con relación a la estabilidad económica de la empresa se encuentra en un punto favorable debido a que sus niveles de endeudamiento y rentabilidad son controlados y manejados de manera óptima por su parte lo que sucede como consecuencia que esta genere más utilidad y ganancia para seguir funcionando en el mercado. Los resultados obtenidos de la evaluación de los indicadores de rentabilidad se determina que el margen bruto de una periodo a otro disminuyo en pocas partes aun así no es favorable para la empresa, en margen operacional es favorable debido al incremento de ganancias, el margen neto tal igual es favorable; el rendimiento sobre el activo de la misma manera que sobre el pasivo son favorables para la empresa lo que significa que existirán más ganancias para la misma. Dados los resultados establecidos por medio de los indicadores financieros con relación a la estabilidad económica de la empresa se encuentra en un punto favorable debido a que sus niveles de endeudamiento y rentabilidad son controlados y manejados de manera óptima por su parte lo que sucede como consecuencia que esta genere más utilidad y ganancia para seguir funcionando en el mercado. Por lo tanto, se concluye que la aplicación de los indicadores financieros son herramientas de carácter fundamental para conocer, analizar la situación económica y financiera de la empresa, en este caso la empresa se encuentra en un punto favorable, de esta manera también se recomienda no exceder con los niveles de endeudamiento, además de mantener el nivel de venta óptimo para generar utilidades con el fin de ser estable económicamente y mantenerse en el mercado. Dados los resultados en el nivel de endeudamiento se recomienda no exceder los niveles recomendados para cada indicador, también mantener el nivel de cobertura de interés para así lograr cubrir con los gastos financieros que se mantengan en el día a día, también una planificación sumamente revisada y analizada al momento de manejar algún financiamiento con terceros. Con respecto a los niveles de rentabilidad se recomienda no descuidar el nivel de utilidad bruta ya que esta se da dependiendo del nivel de ventas que se mantiene en la empresa, así mismo sus niveles de utilidad neta y operacional deben ser revisados con relación a sus beneficios económicos, de la misma manera los rendimientos sobre activo y patrimonio se requiere medir periódicamente la eficiencia de la administración de los mismos. Este trabajo se desarrolla gracias a los medios de comunicación, dado que la información financiera de la procesadora de alimentos se obtiene en el portal web de la Superintendencia de Compañías, debido a que esta es información pública y disponible para cualquier persona que la necesite según la Ley Orgánica de Transparencia y Acceso a la Información Pública, como fin la información obtenida es de suma importancia para el desarrollo de la investigación. Luego de examinar, analizar y conocer estos resultados, el beneficio de estos procesos será tomar las decisiones correctas para mantener la continuidad de la empresa y así mantener una rentabilidad económica estable, cumpliendo propósitos y metas, las cuales ayudaran al desarrollo de la misma e incluso de la situación económica del país debido a que existe una demanda y oferta dentro del mercado.
Keywords: INDICADORES FINANCIEROS; ENDEUDAMIENTO; RENTABILIDAD; ESTABILIDAD ECONÓMICA